Relationship between quality of life and socio-emotional competencies: Systematic review - Redondo Mendoza, Ciro Ernesto; Zapata Rueda, Carla María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The quality of life and the development of socio-emotional skills marks a very important level of interrelation that needs to be revealed. Objective: To analyze empirical research that has raised in its theoretical criteria, the relationship between quality of life and the development of socio-emotional skills. It is based on the PRISMA statement for the preparation of systematic reviews. The analyzed studies evidenced ideas that allude to an interrelation between these two variables. Conclusion: The relationship between quality of life and socioemotional competencies is interdependent. In optimal conditions of quality of life there is adequate development of socio-emotional skills and vice versa.